Trends and Perceived Impact of Social Media as a Persuasive Technology for Business in Malaysia - Hassan, Shahizan; Shiratuddin, Norshuhada; Hashim, Nor Laily; Abd Salam, Sobihatun Nur; Sajat, Mohd Samsu (Malaysian Communications and Multimedia Commission (MCMC), 2014)
Despite its popularity and wide recognition as an effective and persuasive technology in business, studies on the trends and impact of social media (SM) especially in the context of developing countries, have yet to be firmly established. As such, this study attempts to ascertain the trends and perceived impact of SM as a persuasive technology for Small and Medium Enterprises (SMEs) in Malaysia. The methodology comprised five phases: content analysis of current literature; survey on the perception of users regarding SM usage for business; interviews and workshops to gain insights on the trends and impact of SM in business; data integration and analysis and lastly, documentation of research. The target population consisted of SM users in Malaysia i.e. company owners, managers, executives, and employees. Simple random sampling was employed to obtain samples for the survey and interview. The findings show that the overall percentage of SM usage among SMEs was relatively low, at about 20%. In addition, the interview participants believed that SM had a significant impact on their businesses and therefore could be considered as a persuasive tool to attract customers. This is supported by the outcome of the survey which showed that the majority of SM users perceived that SM content could persuade people to purchase products or services. Furthermore, it was found that SM content could also influence purchasing decisions.